In vitro direct plant regeneration and Agrobacterium‐mediated transformation of lucerne (Medicago sativa L.). (27th October 2012) - Kumar, S.; Tiwari, R.; Chandra, A.; Sharma, A.; Bhatnagar, R. K.
Abstract In vitro direct plant regeneration of lucerne was achieved by simultaneous application of thidiazuron (TDZ) and 6‐benzyladenine (BA) in Murashige and Skoog (MS) medium. Seedlings were germinated and grown for 6 d on growth regulator–containing MS medium. The shoot tip, consisting of the apical meristem along with parts of the cotyledonary leaves and hypocotyl, was then cultured on a medium containing the growth regulator(s). Adventitious budding of the shoot tip was promoted synergistically by treatment with TDZ and BA, and a maximum of thirty‐five shoots per explant was obtained on a medium supplemented with 2 mg L−1 TDZ and 1 mg L−1 BA. Plant regeneration frequency varied from 67 to 93%, and five Indian lucerne cultivars responded well to the regeneration protocol. The Agrobacterium‐mediated transformation frequency from co‐cultivated explants was 13% following multiple shoot induction. Southern analysis of the T0 plants and T1 progenies confirmed stable inheritance of the hpt marker gene. Agrobacterium infection of the explant caused a significant reduction in the plant regeneration frequency (23%) and the number of shoots induced (11) when compared with uninfected explants. A single shoot tip provided sufficient material to regenerate and establish twenty‐seven lucerne plants, whereas only nine plants could be regenerated from an Agrobacterium co‐cultivated explant. This transformation protocol could represent a valuable improvement over existing ones for lucerne.